2020
DOI: 10.1007/s11085-020-09980-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Impurities on Alloy Behavior in Supercritical CO2 at 700 °C

Abstract: As part of round robin testing, specimens of commercial alloys 316, 120, 625 and 740 were exposed to 20 MPa research grade CO2 at 700°C for up to 1500 h. The first set of specimens had higher mass gain likely due to impurities not flushed from the autoclave at startup. After this issue was corrected, an identical set of specimens exhibited lower mass gains for both the Fe-and Ni-based alloys. The differences in reaction products were characterized to understand the effect of impurities under these conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The mass gains and oxide thicknesses correlate quite well with one another and the calculated rate constants are in the same order of magnitude as those of commercial alloys studied under similar conditions [32,38,70]. Interestingly, the oxidation rate constant for 282 alloy (k p = 2.9 × 10 -8 mg 2 cm −4 s −1 ) in sCO 2 was close to that of a Ni-based alloy with similar Cr, Ti, and Al concentrations (k p = 1.7 × 10 -8 mg 2 cm −4 s −1 ), when studied in air at 750 °C for 2000 h [63].…”
Section: The Effect Of Ti Additionsupporting
confidence: 61%
See 1 more Smart Citation
“…The mass gains and oxide thicknesses correlate quite well with one another and the calculated rate constants are in the same order of magnitude as those of commercial alloys studied under similar conditions [32,38,70]. Interestingly, the oxidation rate constant for 282 alloy (k p = 2.9 × 10 -8 mg 2 cm −4 s −1 ) in sCO 2 was close to that of a Ni-based alloy with similar Cr, Ti, and Al concentrations (k p = 1.7 × 10 -8 mg 2 cm −4 s −1 ), when studied in air at 750 °C for 2000 h [63].…”
Section: The Effect Of Ti Additionsupporting
confidence: 61%
“…Only the external oxide has been taken into account and any internal degradation has been excluded from the thickness measurements. Since similar alloys have been reported to follow parabolic oxidation kinetics [32,33], Eq. 3 has been used to calculate parabolic rate constants presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The explanation is that with the addition of O2, the rate of Cr diffusion will be accelerated and lead to formation of the oxide layer with more defects. The results of another study [79] indicated that the existence of O2 led to a thicker oxide layer and higher mass gain.…”
Section: Effect Of Omentioning
confidence: 96%
“…Essential corrosion data for model development and validation should include measured concentration profiles after exposures at the temperatures of interest (700-800°C) for different times. For exposures in sCO 2 , depletion of the alloying element forming the protective oxide can be correlated to the temporal evolution of specific mass change measurements for the three alloys (740H, 282 and 625), since these alloys have been reported to form compact and protective Cr-rich Cr 2 O 3 scales up to 800°C [2,4,[18][19][20][21][22][23][24][25]. However, for exposures in molten chloride salts, a combination of the extremely low fraction of species reacting in the boundary regions (a few microns) between phases or molecular regions and nonequilibrium reaction kinetics provide challenges in identifying corrosion products.…”
Section: Subtask 11: Identifying Materials Based On Chosen Applicationmentioning
confidence: 99%